Speaking in behalf of the person with dementia in home-based care. A qualitative study of collaboration between formal and family caregivers in Sami and Norwegian municipalities. - Larsen, Lill Sissel Sverresdatter (UiT The Arctic University of Norway, 2017)
The papers of this thesis are not available in Munin. Paper I: Larsen, L. S., Normann, H. K., Hamran, T.: «Processes of user participation among formal and family caregivers in home-based care for persons with dementia”. Published version available in Dementia 2015, 16(2):158-177. Manuscript version available in Munin at http://hdl.handle.net/10037/10158 Paper II:.Larsen, L. S., Normann, H. K., Hamran, T.: «Collaboration between Sami and non-Sami formal and family caregivers in rural municipalities”. Published version available in Ethnic and Racial Studies 2015, 39(5):821-839. Manuscript version available in Munin at http://hdl.handle.net/10037/10348 Paper III: Larsen, L. S., Normann, H. K., Hamran, T.: «Continuity of home-based care for persons with dementia from formal and family caregivers’ perspective. Published version available in Dementia 2016. Manuscript version available in Munin at http://hdl.handle.net/10037/10155 Studien «Speaking on behalf of the person with dementia in home-based care» viser en rekke krevende barrierer for samhandling i demensomsorg i norske kommuner. Disse barrierene har negativ påvirkning på hvilke hjelpetilbud som tilbys og hvordan familier nyttiggjør seg disse, noe som igjen har betydning for oppnåelse av helsepolitiske mål og pasientrettigheter. I kommuner med både norsk og samisk befolkning forsterkes flere av disse barrierene. Studien får frem beskrivelser av samhandling og barrierer for samhandling mellom helsepersonell og pårørende i demensomsorg i hjemmetjenester i rurale kommuner hvor befolkningen har samisk og norsk tilhørighet. Samhandling er initiert både av pasienter og pårørendes behov, men også helsepolitiske strategier for at pasienter skal kunne bo lengst mulig hjemme, at pårørende får nødvendig støtte og at pasienters selvbestemmelse ivaretas. Doktorgradsavhandlingen bygger på 18 semistrukturerte intervju, feltarbeid der demensteam ble fulgt, tematisk innholdsanalyse og videre teoretiske analyser med bruk av analytiske begrep som etnisk tilhørighet, ...